2022
DOI: 10.1007/s10586-022-03704-1
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Gramian Angular Field classification for edge internet of energy applications

Abstract: With adverse industrial effects on the global landscape, climate change is imploring the global economy to adopt sustainable solutions. The ongoing evolution of energy efficiency targets massive data collection and Artificial Intelligence (AI) for big data analytics. Besides, emerging on the Internet of Energy (IoE) paradigm, edge computing is playing a rising role in liberating private data from cloud centralization. In this direction, a creative visual approach to understanding energy data is introduced. Bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Because of the 2D nature of the data, a plethora of DL methods can be employed, e.g., Convolutional Neural Networks (CNN), Long-Short Term Memory (LSTM), etc. to classify the data and gain useful insights with significantly lower computational time [20].…”
Section: D Gaf Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the 2D nature of the data, a plethora of DL methods can be employed, e.g., Convolutional Neural Networks (CNN), Long-Short Term Memory (LSTM), etc. to classify the data and gain useful insights with significantly lower computational time [20].…”
Section: D Gaf Datamentioning
confidence: 99%
“…5, sample GAFs are classified based on a modified EfficientNet-B0 classifier (CNN with transfer learning). The algorithm, explained in detail in [20], classifies the data based on average normalized values of the GAF data, i.e., a GAF is normal is its average normal value within its duration window is less than a specified abnormality threshold, and vice versa. It is worth mentioning that the model is trained on a Linux instance while the testing has been carried out on an ODROID-XU4 board to signify the merits of 2D GAF classification in terms of classification computational performance, e.g.…”
Section: D Gaf Datamentioning
confidence: 99%
“…Edge-cloud collaboration has been introduced for fault diagnosis since its conceptual proposal. Several methods have been developed, including multi-level fault diagnosis [1,2] and edge-inferencing after cloud-trained [3][4][5][6][7][8][9][10][11][12][13] . Multi-level fault diagnosis is to deploy simple models at the edge for rough classification to filter normal data and reduce the inference time.…”
Section: Introductionmentioning
confidence: 99%
“…When a fault occurs, a second-level fault diagnosis is performed in the cloud to infer the details of a fault [1,2] . Edgeinferencing after cloud-trained trains a diagnostic model in the cloud and then deploys it to edge for inference [3][4][5][6][7][8][9][10] . However, a lightweight model is usually adopted due to the limited computing resources on the edge side [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…A potential solution involves the reorganization of the signal and explicit modeling of the temporal dependencies to gain a deeper understanding of the dynamics in a time series. Certain studies [8][9][10][11][12][13] have demonstrated the ease of extracting of information from high-dimensional data. Silva et al [8,9] extended the recurrence plots (RP) paradigm for a time series with compressed distance and proposed to process the RP as grayscale texture images.…”
Section: Introductionmentioning
confidence: 99%